2005
DOI: 10.1002/art.21145
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB protects Behçet's disease T cells against CD95‐induced apoptosis up‐regulating antiapoptotic proteins

Abstract: Objective. To determine whether prolongation of the inflammatory reaction in patients with Behçet's disease (BD) is related to apoptosis resistance and is associated with the up-regulation of antiapoptotic factors.Methods. The percentage of cell death was evaluated by flow cytometry in peripheral blood mononuclear cells from 35 patients with BD and 30 healthy volunteers. The expression levels of antiapoptotic factors and NF-B regulatory proteins were measured using Western blotting and immunohistochemical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 52 publications
(76 reference statements)
0
36
0
Order By: Relevance
“…2E). Behcet's disease resting T lymphocytes (36) and MCF-7 cells were used as positive controls. Thus, cFLIP L and PED/PEA-15 up-regulation in thyroid cancer cells may confer resistance to CD95-induced apoptosis.…”
Section: Il-4 and Il-10 In Thyroid Cancermentioning
confidence: 99%
“…2E). Behcet's disease resting T lymphocytes (36) and MCF-7 cells were used as positive controls. Thus, cFLIP L and PED/PEA-15 up-regulation in thyroid cancer cells may confer resistance to CD95-induced apoptosis.…”
Section: Il-4 and Il-10 In Thyroid Cancermentioning
confidence: 99%
“…These cytokines detected in patients with active disease point to a polarized Th1 immune response, as suggested by in vitro and in vivo studies of experimental autoimmune uveoretinitis [11]. We have also documented increased numbers of T lymphocytes expressing the gammadelta receptor that overproduce TNF in patients with active disease [12] and more recently a role of NF-kB in protecting T cells against CD95 induced apoptosis down-regulated by thalidomide, a TNF inhibiting agent [13].…”
Section: Introductionmentioning
confidence: 72%
“…[15][16][17] Accordingly, high expression of c-FLIP is generally observed in chronic inflammatory diseases such as rheumatoid arthritis, multiple sclerosis, and Behçet disease. 18,[40][41][42] It was, however, also reported that NF-B RelA-deficient mouse embryonic fibroblasts do not differ in tumor necrosis factor (TNF)-induced c-FLIP expression compared with wild-type cells, suggesting that c-FLIP expression can occur independently of NF-B. 43 In contrast to CsA, we found that rocaglamide, which has been shown to inhibit NF-B as well as NFAT transcription factors, 25,26 impaired the expression of both c-FLIP long and c-FLIP short , suggesting that NF-B indeed contributes to c-FLIP gene regulation in T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Inducible c-FLIP expression in peripheral T cells has primarily been linked to the nuclear factor-B (NF-B) signaling pathway [15][16][17][18] ; however, other transcription factor-binding sites do exist in the FLIP promoter. In addition, studies in various tumor cell lines have indicated a regulation of c-FLIP expression by the PI3K/Akt and Erk/MAP kinase pathway.…”
Section: Introductionmentioning
confidence: 99%